Effect of Moringa Leaf Extract on Growth and Yield of Tomato - Bari, Masroor Ul Hassan; Alam, Mahnoor Muhammad Shah; Khan, Muhammad Suleman; Sundas, Faria; Razaullah, Syed (MultiTech Publisher, 2024)
This study delves into the effects of Moringa oleifera leaf extract (0%, 3%, 6%, and 9% V/V) on tomato plant growth. Employing a randomized design, the 6% concentration emerges as a key player, significantly boosting performance. Results include heightened leaf count, increased height, larger and heavier fruits, improved firmness, volume, and elevated chlorophyll content. Intriguingly, the 9% concentration indicates a potential for increased branches, suggesting enhanced fruit production. Fruit pH remains consistently unaffected across treatments. Integrating moringa leaf extract, particularly at 6% and 9%, not only enhances tomato plant productivity and fruit quality but also lays the ground work for sustainable cultivation practices. This research contributes valuable insights for optimizing growth conditions, there by offering a pathway to improving overall crop yield and agricultural sustainability.